2017
DOI: 10.1016/j.neuroimage.2017.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Time Interleaved MultiSlice (STIMS) for Rapid Susceptibility Weighted acquisition

Abstract: T2* weighted 3D Gradient Echo (GRE) acquisition is the main sequence used for Susceptibility Weighted Imaging (SWI) and Quantitative Susceptibility Mapping (QSM). These applications require a long echo time (TE) to build up phase contrast, requiring a long repetition time (TR), and leading to excessively lengthy scans. The long TE acquisition creates a significant amount of unused time within each TR, which can be utilized for either multi-echo sampling or additional image encoding with the echo-shift techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
0
18
1
Order By: Relevance
“…A ten-day scan cannot serve as a routine protocol. In recent years, compressed sensing (CS) has emerged as a new accelerated imaging technique, which enables reconstruction of under sampled data by exploiting image sparsity (Lustig et al 2007;Liang et al 2009;Wu et al 2014;Bilgic et al 2017;Wang et al 2018). There are three essential aspects for CS: sparsity, sampling pattern, and reconstruction (Lustig et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A ten-day scan cannot serve as a routine protocol. In recent years, compressed sensing (CS) has emerged as a new accelerated imaging technique, which enables reconstruction of under sampled data by exploiting image sparsity (Lustig et al 2007;Liang et al 2009;Wu et al 2014;Bilgic et al 2017;Wang et al 2018). There are three essential aspects for CS: sparsity, sampling pattern, and reconstruction (Lustig et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting decrease in acquisition time may facilitate broader clinical application of SWI, especially in motionprone populations (eg, children, elderly, and acutely ill patients). Wave-CAIPI has shown the potential to accelerate susceptibilityweighted acquisitions in healthy volunteers 8,9 but has not been systematically evaluated in a clinical setting.…”
mentioning
confidence: 99%
“…We should also make allowance for the specific absorption rate when optimizing the profile, because the specific absorption rate is already relatively large for adiabatic inversion‐recovery pulses. After this part is done, a 2D interleaved ViSTa, or a SMS interleaved ViSTa (similar to the recently reported STIMS sequence, is applicable. Our initial experiment revealed that at least 6 SMS slice groups could fit in the current timing configuration. To mitigate the wrap‐around part of the imperfect slab excitation profile, the presented study slightly reduced (by a factor of 0.9) the excitation thickness of the RF, which is in the same principle of oversampling along the partition direction, but was still capable to cover the whole brain.…”
Section: Discussionmentioning
confidence: 99%